Optimization of P3HT:PCBM Bulk Heterojunction Polymer Solar Cells: Effects of Annealing Temperature and Active Layer Composition - Hardeli, Hardeli; Sanjaya, Hary; Harahap, Riri Indah Nitami; Permatasari, Putri (Universitas Andalas, 2025)
P3HT:PCBM-based polymer solar cells have demonstrated potential as an affordable substitute for conventional silicon-based photovoltaics. The performance of P3HT:PCBM bulk heterojunction solar cells is examined in this work in relation to the annealing temperature and the composition of the active layer. The morphology of the active layer was characterized using SEM, while the electrical properties were measured using current-voltage (I-V) characterization. Our findings show that 150°C is the ideal annealing temperature, resulting in the maximum power conversion efficiency (PCE) of 2.58%. SEM analysis revealed that this temperature produces the most homogeneous surface morphology. Additionally, a P3HT:PCBM ratio of 3:1 resulted in the best device performance, with a PCE of 4.36%. Short-circuit current and open-circuit voltage increase when the blend's P3HT level increases. These results offer important information for optimizing the production of P3HT:PCBM-based polymer solar cells, which could lead to increased organic photovoltaic device efficiency and possible commercial outcomes.